Muscle Flap Closure following Complex Spine Surgery: A Decade of Experience. Issue 5 (November 2020) - Wright, Matthew A.; Weinstein, Andrew L.; Bernstein, Jaime L.; Franck, Philipp; Lara, Daniel O.; Samadi, Arash; Cohen, Leslie E.; Härtl, Roger; Baaj, Ali A.; Spector, Jason A.
Abstract : Background: Advances in surgical technology and adjuvant therapies along with an aging and increasingly morbid U.S. population have led to an increase in complex spine surgery. With this increase comes an elevated risk of complications, including those related to the surgical wound, with some studies demonstrating wound complication incidences approaching 45 percent. The authors hypothesize that immediate muscle flap closure improves outcomes in high-risk patients. Methods: Three hundred one consecutive index cases of spinal wound closure using local muscle flaps performed by the senior author at a single institution between 2006 and 2018 were reviewed. The primary outcome was major wound complication (reoperation and/or readmission because of surgical-site infection, late infection, dehiscence, seroma, or hematoma). Logistic regression analysis was performed to identify predictors of this endpoint. Results: Major wound complications occurred in 6.6 percent of patients (reoperation, 3.6 percent; readmission, 3.0 percent), with a 6.0 percent infection rate and five cases requiring instrumentation removal because of infection. Risk factors identified included radiotherapy (OR, 5.9; p = 0.004), age 65 years or older (OR, 2.8; p = 0.046), and prior spine surgery (OR, 4.3; p = 0.027). The incidence of major wound complication increased dramatically with each additional risk factor. Mean drain dwell duration was 21.1 ± 10.0 days and not associated with major wound complications, including infection (OR, 1.04; p = 0.112). Conclusions: Immediate local muscle flap closure following complex spine surgery on high-risk patients is associated with an acceptable rate of wound complications and, as these data demonstrate, is safe and effective. Consideration should be given to immediate muscle flap closure in appropriately selected patients. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.